Safety of Inulin and Sinistrin: Combining Several Sources for Pharmacovigilance Purposes - Bui, T-V.; Prot-Bertoye, C.; Ayari, H.; Baron, S.; Bertocchio, J-P.; Bureau, C.; Davis, P.; Blanchard, A.; Houillier, P.; Prie, D.; Lillo-Le Louet, A.; Courbebaisse, M. (Frontiers in Pharmacology, 2021)
Abstract (Word count 240/250 max) Introduction: Inulin and its analog sinistrin are fructose polymers used in the food and pharmaceutical industries. In 2018, The French National Agency for the Safety of Medicines and Health Products (ANSM) decided to withdraw products containing sinistrin and inulin due to several reports of serious hypersensitivity reactions, including a fatal outcome. Objective: To assess the safety of inulin and sinistrin use in France. Methods: We searched multiple sources to identify adverse reactions (ARs) to inulin or sinistrin: first, classical pharmacovigilance databases including the French Pharmacovigilance (FPVD) and the WHO Database (VigiBase); second, data from a clinical trial, MultiGFR; third, data regarding current use in an hospital. All potential ARs to inulin or sinistrin were analyzed with a focus on hypersensitivity reactions and relationships to batches of sinistrin. Results: From 1991 to 2018, 134 ARs to inulin or sinistrin were registered in the FPVD or VigiBase. Sixty-three cases (47%) were classified as serious, and 129 cases (96%) were hypersensitivity reactions. We found an association between a batch of sinistrin and the occurrence of hypersensitivity reactions. During the MultiGFR clinical trial, 7 patients (7/163 participants) had an AR; of these, 4 were hypersensitivity reactions including one case of grade 4 anaphylactic shock. In the hospital, no ARs were observed. In the literature, ARs to inulin and sinistrin are very rarely reported and mostly benign. Conclusion: Most ARs to inulin and sinistrin are hypersensitivity reactions that appear to be associated with sinistrin batches.